Penerapan Pembelajaran Kooperatif Tipe TPS (Think Pair Share) untuk Meningkatkan Hasil Belajar PKn di MI Negeri 1 Yogyakarta - Erni Yuliati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
The quality of education today still looks less satisfying. The size of education quality can be seen from the academic achievement of students, namely the value of exams and the influence of learning outcomes on daily life. The success of education is determined by many factors, among them the teacher factor, the teachers who have skills in the learning process, the ability to choose a learning model that can improve students' learning skills and outcomes. One of the ways teachers can do is to implement a cooperative learning model of TPS type (Think Pair Share). This research was conducted at MIN 1 Yogyakarta. This research is a class action research (PTK). Data analysis results showed that generally students ' absorption of learning materials showed significant improvement. Based on the results of the evaluation, the increased learning ability of students in cycle I reached 70.6 and increased to 80.2 in cycle II. The average daily replay value has also increased to 70.3 and becomes 83.5 after the implementation of the TPS type Cooperative learning. This indicates that the implementation of the TPS type Cooperative learning can improve the student's learning outcomes.